Assessing organisational readiness of SMEs towards digital transformation through an examination of organisational characteristics - Myllyniemi, Matilda (My University, 2023)
This thesis studies SMEs’ organisational characteristics effect on their organisational readiness towards digital transformation. The adoption of new digital technology has become necessary for companies to remain competitive, leading to digital transformation. Particularly impacted by the disruptive nature of digital transformation are small and medium-sized businesses (SMEs). According to estimates, between 66% and 86% of all organisations are not effectively undertaking digital transformation. The figure may even be higher for SMEs because they are under more pressure to digitally transform while at the same time having difficulties to go through digital transformation due to, e.g., limited resources. Relatively few studies have been conducted on the digital transformation of small and medium-sized companies. Overall, the study of digital transformation is still in its infancy; interest in it only began to grow in the past ten years. The research question of the thesis is “How do SMEs’ organisational characteristics affect their organisational readiness towards digital transformation?”. The research question is answered through a literature review and an empirical study. Qualitative research was executed for this thesis to generate new ideas and develop the theory presented in the literature review further. A multiple case study was carried out using the Gioia method. Empirical data was collected from half-structured interviews that were held in five SMEs of different sizes and industries. Friendly audit case and key data source technique were also used to modify the interview questions and select interviewees that could provide more content when answering the interview questions. The empirical research showed that competitiveness is a root cause for companies striving to digitally transform. All drivers and objectives for digital transformation are based on companies’ need to stay competitive. Other important objectives for digital transformation, according to the empirical research, are product innovation and increasing customer satisfaction. Furthermore, the study revealed the most important characteristics that can enhance or weaken digital transformation readiness in an organisation. Enhancing characteristics are small IT infrastructure, small size and simple internal structure, adaptability, and flexibility. The weakening characteristics are low level of expertise in IT, lack of resources and dependency on third parties. The most emphasized characteristic weakening the organisational readiness of SMEs was found to be the lack of resources. Improving resource situation is a key factor in improving SMEs’ organisational readiness towards digital transformation. As an outcome of this thesis, a framework is provided for analysing the organisational readiness for digital transformation based on SMEs’ characteristics. It sums up all the topics that are explored in this thesis. Organisational readiness towards digital transformation can be evaluated through organisational enablers and barriers, whilst also considering the drivers and objectives for digital transformation. Additionally, especially in SMEs, it is important to understand that characteristics have a holistic effect on the digital transformation readiness of SMEs and can either improve or weaken it. This thesis contributes to a research area that is yet studied too little by increasing understanding in SMEs’ organisational readiness towards digital transformation. It also provides useful tools to SMEs while also offering important focus areas for future research.
Keywords: digital transformation, organisational readiness, SMEs, organisational characteristics